2015
DOI: 10.1136/sextrans-2015-052152
|View full text |Cite
|
Sign up to set email alerts
|

Meeting sexual partners online: associated sexual behaviour and prevalent chlamydia infection among adolescents in Norway: a cross-sectional study

Abstract: This population-based study suggests that internet-partners are common among adolescents in Norway, and the reason for meeting them was more strongly associated with additionally reporting sexual risk behaviours and prevalent chlamydia infection than the internet itself as a meeting venue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…China has been experiencing vast economic and information technology developments in the past decades, allowing an unprecedented number of people to get access to Internet [28]. The Internet has been gaining tremendous popularity among Chinese MSM, as many gay-friendly online platforms for interaction have now been established (e.g., chat rooms, gay websites, web-based gay apps, instant messaging) which help them to expand their social networks and facilitate sexual hook-ups, saving travel time and cost and improving the likelihood of finding compatible sexual partners [28,31,32]. In contrast, traditional venue-based sex-seeking has disadvantages such as time and location constraints, concerns about privacy disclosure, encountering stigma, trouble with legal authorities, and fewer opportunities to find compatible partners [33].…”
Section: Discussionmentioning
confidence: 99%
“…China has been experiencing vast economic and information technology developments in the past decades, allowing an unprecedented number of people to get access to Internet [28]. The Internet has been gaining tremendous popularity among Chinese MSM, as many gay-friendly online platforms for interaction have now been established (e.g., chat rooms, gay websites, web-based gay apps, instant messaging) which help them to expand their social networks and facilitate sexual hook-ups, saving travel time and cost and improving the likelihood of finding compatible sexual partners [28,31,32]. In contrast, traditional venue-based sex-seeking has disadvantages such as time and location constraints, concerns about privacy disclosure, encountering stigma, trouble with legal authorities, and fewer opportunities to find compatible partners [33].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this pattern has also been seen in the other two population studies with a significant relationship between STIs and searching for or meeting partners online among men but not women. [4,5] Findings from other studies have been mixed as to whether STI diagnoses are related to either finding or searching for sexual partners online. [1][2][3][4]17, 20] A number of studies have reported on HIV testing history among gay men and tend to find that men who use apps are more likely to have been tested for HIV.…”
Section: Principal Resultsmentioning
confidence: 95%
“…Several similar studies have used biological measurement to ascertain STI prevalence, a more robust measure. [2,4,5] However, when asked, most survey participants reported that they had answered questions truthfully and were either not embarrassed or only slightly embarrassed by the questions. [7] Implications Understanding the extent and the characteristics of people who are most likely to use these technologies to meet new sexual partners assists the organizations who are responsible for HIV/STI prevention programs to identify places and populations where they can focus their health promotion and testing initiatives.…”
Section: Limitationsmentioning
confidence: 99%
“…trachomatis infection, an increased number of sexual partners was found, thus agreeing with previous reports describing a similar association not only with C . trachomatis , but with almost all STI [ 28 30 ]. The fact of having had many sexual partners also implies being involved in risky sexual behaviour thereby facilitating contagion by more than one type of microorganism and hampering clearance of infection [ 3 , 10 , 31 33 ].…”
Section: Discussionmentioning
confidence: 99%